FISIOLOGIS TANAMAN CABAI MERAH (Capsicum annuum L.) TERHADAP CEKAMAN KEKERINGAN DI LAHAN PESISIR - Sunandar; Fahrurrozi; Pringky Okta Saputra; Ferdian Noor Widya Utomo; Pianto Ramadhan Prastio; Sultan Imam Al-Fikri; Victorianus Chandra Suwandana; Mantegna Gordi Ruviken; Mantegna Gordi Ruviken (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2025)
Red chili pepper (Capsicum annuum L.) is a major horticultural crop with high economic importance and a vital role in meeting food demands. Its demand continues to increase alongside population growth, yet production is often limited by drought stress, particularly in coastal regions characterized by sandy soils, low water-holding capacity, and high salinity. This review aims to assess the physiological responses of red chili plants to drought stress in coastal environments and to identify adaptive mechanisms that enhance plant tolerance. Drought stress has been reported to decrease photosynthetic activity, chlorophyll concentration, and transpiration rate due to stomatal closure. Plants counteract water deficit by accumulating osmolytes such as proline and soluble sugars and by enhancing antioxidant enzyme activities, including superoxide dismutase (SOD) and peroxidase (POD), to mitigate oxidative damage. Drought conditions also result in significant reductions in plant height, flower number, and fruit yield, reaching up to 51%. These adaptive mechanisms highlight the importance of developing drought-tolerant cultivars and applying water-efficient cultivation techniques, such as silver-black plastic mulch and drip irrigation, to sustain red chili productivity in drought-prone coastal regions.